Liberalizing Trade in Agriculture: Developing Countries in Asia and the Post-Doha Agenda - Wilson, John S. (World Bank, Washington, D.C., 2013)
The author provides an overview and data relevant to the interests of developing countries as they engage in continuing agricultural trade negotiations set forth in the World Trade Organization Ministerial held in Doha, Qatar in November 2001. He examines country performance in agricultural trade, income levels, and population characteristics, with a focus on developing country members of the Asian Development Bank. The author concludes that trends in agricultural trade in the past 10 years are quite heterogeneous across developing regions. Shares of agriculture in GDP are still high in the East Asia and Pacific and South Asia regions. Moreover, data indicate that trade reform in export partners, particularly OECD countries, will affect a significant share of the population in these developing countries, resulting in rural poverty alleviation. Trade liberalization is expected to benefit net exporter countries, particularly those that are highly open to trade. What is also important, but often neglected, is a country's pattern of specialization between domestic supply and exports. The impact of trade reform through the WTO negotiations, particularly reforms undertaken in exporting partners can therefore have important implications in the post-Doha development agenda.